Strategies for Integrating Multicultural Education and Religious Education to Strengthen the Multicultural Character of Elementary School Students - Barsihanor, Barsihanor; Rofam, Galuh KMR; Hafiz, Abdul (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2024)
Religious education and multicultural education in elementary schools are considered very important in addressing the increasing issue of moral decay among children. This study aims to describe the strategy of integrating the interconnection of religious and multicultural education in strengthening the character of elementary school students. This study uses a qualitative approach of the case study type with the objects of the principal, teachers, and students. Research data were collected through observation, interviews, and documentation. The collected data were then analyzed through data reduction, data presentation, and conclusion drawing. Researchers use triangulation techniques and triangulation sources to obtain data validity. This study found that integrating the interconnection of religious education and multicultural education strengthens the character of elementary school students by integrating-interconnecting certain values in the curriculum and the learning process, namely equality, unity, justice, kinship, tolerance, and love of peace. The results of this study not only provide theoretical contributions to character formation through religious and multicultural education and offer practical insights for elementary schools in forming students' characters through the integration of religious and multicultural education.